A new hepatitis E virus genotype 2 strain identified from an outbreak in Nigeria, 2017 - Bo Wang; Olusola Anuoluwapo Akanbi; Dominik Harms; Olufisayo Adesina; Folakemi Abiodun Osundare; Dhamari Naidoo; Isabel Deveaux; Opeayo Ogundiran; Uzoma Ugochukwu; Nwando Mba; Chikwe Ihekweazu; C.-Thomas Bock (Virology Journal, 2018)
Abstract Background In 2017 the Nigerian Ministry of Health notified the World Health Organization (WHO) of an outbreak of hepatitis E located in the north-east region of the country with 146 cases with 2 deaths. The analysis of the hepatitis E virus (HEV) genotypes responsible for the outbreak revealed the predominance of HEV genotypes 1 (HEV-1) and 2 (HEV-2). Molecular data of HEV-2 genomes are limited; therefore we characterized a HEV-2 strain of the outbreak in more detail. Finding The full-length genome sequence of an HEV-2 strain (NG/17–0500) from the outbreak was amplified using newly designed consensus primers. Comparison with other HEV complete genome sequences, including the only HEV-2 strain (Mex-14) with available complete genome sequences and the availability of data of partial HEV-2 sequences from Sub-Saharan Africa, suggests that NG/17–0500 belongs to HEV subtype 2b (HEV-2b). Conclusions We identified a novel HEV-2b strain from Sub-Saharan Africa, which is the second complete HEV-2 sequence to date, whose natural history and epidemiology merit further investigation.